2015
DOI: 10.1007/s12207-015-9242-2
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Issues in Geropsychology: Clinical and Forensic Perspectives

Abstract: Ethical practice and decision making in geropsychology require an awareness and understanding of the ethical issues and challenges that are commonly encountered when working with older adults in clinical and forensic contexts. Although multiple resources are available to assist practitioners with identifying common ethical issues and challenges, experienced colleagues often serve as one of the richest sources of information. The purpose of this article was to tap the ethical knowledge of psychologists who have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…In terms of managing elder abuse and euthanasia, the insight offered in this study helps to reconcile the ethical resources available with the nuances of clinical practice (Bush et al, 2015). In Australia where (a) there is no current legal reporting requirement for elder abuse and (b) euthanasia is not legalized and voluntary assisted dying is only legal in one state, many questions exist about psychologists’ ethical and legal responsibilities around reporting.…”
Section: Discussion and Clinical Implicationsmentioning
confidence: 99%
“…In terms of managing elder abuse and euthanasia, the insight offered in this study helps to reconcile the ethical resources available with the nuances of clinical practice (Bush et al, 2015). In Australia where (a) there is no current legal reporting requirement for elder abuse and (b) euthanasia is not legalized and voluntary assisted dying is only legal in one state, many questions exist about psychologists’ ethical and legal responsibilities around reporting.…”
Section: Discussion and Clinical Implicationsmentioning
confidence: 99%
“…A common ethical dilemma in the clinical practice of geriatric mental health practitioners is the requirement to balance the patients’ autonomy with their welfare (beneficence). 27 While the practitioners wish to support their patients’ rights to make independent decisions regarding their treatments, often, when patients are incapacious and their decisions can be contradictory to their welfare, the practitioners find it challenging to support these decisions. In these circumstances, awareness about the patients’ lifetime values and wishes can help resolve the conflicts.…”
Section: Ethical Challengesmentioning
confidence: 99%
“…almaları için teşvik edilmektedirler (APA, 2004;2014). Bununla ilişkili olarak, ileri yetişkinlerle çalışan alandaki deneyimli psikologlar, geropsikoloji alanında eğitim fırsatlarının artırılması gerektiğini dile getirmektedirler (Bush, Allen, Heck ve Moye, 2015). İleri yetişkin nüfusundaki artışa rağmen çok az psikoloğun ileri yetişkinlere hizmet verme konusunda uzmanlaştığı ve birçok psikoloğun özel bir eğitim ve süpervizyon almadan ileri yetişkinlere hizmet verdiği dikkate alındığında (Hoge, Karel, Zeiss, Alegria ve Moye, 2015), yeterlik ilkesi ile ilgili bu gerekliliklerin yerine getirilmediği söylenebilir.…”
Section: Yeterlikunclassified
“…In addition, it is suggested that education opportunities in geropsychology should be improved. (Bush, Allen, Heck, & Moye, 2015).…”
Section: Competencementioning
confidence: 99%
See 1 more Smart Citation